A Cephalometric Study on the Relationship between the Occlusal Plane, Ala-Tragus and Camper's Lines, in Patients with Angle's Class III Malocclusion - F. Rostamkhani; A. Sahafian; H. Kermani (Tehran University of Medical Sciences, 2005)
Statement of Problem: Considering the importance of the occlusal plane orientation in complete denture prostheses, a study was conducted on the relationship between this plane with ala-tragus and Camper's lines in soft tissue among individuals with class III malocclusion, in Mashhad School of Dentistry. Purpose: The aim of the present study was to define the best soft tissue index by which the location and inclination of the occlusal plane in complete dentures could be established. Materials and methods: The participants consisted of 13 males with Angle's class III occlusal relationship. Radiopaque markers were attached to the intended points on soft tissue and then standard lateral cephalograms were obtained from each subject. The angles between the following lines were measured: Occlusal line (OL), Camper's line (ala-porion), AT1 (ala-superior border of tragus), AT2 (ala- mid-tragus) and AT3 (ala-inferior border of tragus). Results: The mean values and standard deviations calculated from the measured variables are as follows: OL-^AT1, 5.65 (3.95) degrees; OL- ^AT2, 3.19 (2.45) degrees; OL- ^AT3, 2.92 (2.42) degrees and OL- ^Camper, 8.5 (3.83) degrees. Comparison of the results by the ANOVA test exhibited a significant difference (F=3.7, P=0.05). As the OL^-AT3 angle had the lowest value, the occlusal line had a stronger tendency to be parallel to the AT3 line. Conclusion: According to the present study, the inferior border of the tragus is suggested as the posterior point for ala-tragus line orientation.